THE POTENTIAL OF INDONESIAN GRAPHITE AS RDE FUEL MATRIX - Deni Mustika; Sudirman Sudirman; Adel Fisli; I Made Joni; Th. Rina M. (Jurnal Sains Materi Indonesia, 2019)
THE POTENTIAL OF INDONESIAN GRAPHITE AS RDE FUEL MATRIX. The development plan of Ex- perimental Power Reactor (RDE) in Indonesia is non-commercial and leads to the technology type of Pebble Bed Reactor (PBR) - High Temperature Gas Cooled Reactor (HTGR). The fuel used for PBR reactors is kernel dispersed in spherical fuel elements. The matrix used in PBR nuclear fuel is graphite which functions as a neutron moderator, fuel protective material and heat conductor. Domestication of the domestic fuel matrix needs to be conducted to improve national independence. Therefore, it is necessary to do research on the potential of local graphite to be used as RDE fuel matrix. This study focused on the identification and characterization of local and commercial graphite. The results are compared with the literature, how far it is fulfilling nuclear grade graphite for PBR fuel matrix. Characterization of graphite includes phase analysis with XRD, micro- structure with SEM, surface area/porosity, impurities determination with AAS, ICP-OES and NAA, equivalent boron content, carbon content, density, particle size distribution and ash content. The characterization results show that the carbon content obtained was 87.0 ± 4.2% for local graphite and 100% for commercial graphite. Meanwhile, for the purposes of nuclear graphite it requires a carbon content of >99%. The impurity content in local and commercial graphite still does not meet the RDE fuel matrix standard. The results of XRD analysis show that the local graphite phase is the same as the commercial graphite phase, namely the 2H graphite hexagonal crystal system with the lattice group of P 63/mmc. Particle size distribution and surface area of local graphite are higher compared to nuclear graphite literature. The ash content of commercial graphite was 0.236 ± 0.029 and local graphite was 9.587 ± 0.010%. The results of this study indicate that the local graphite from the flotation still requires a further refinement process to obtain local graphite that can be used as a fuel matrix for RDE.